Dayah and Classical Islamic Texts in Contemporary Gayo Land - Qari, Riduan; Ja’far, Ja’far; Iqbal, Muhammad (Fitrah: Journal of Islamic Education, 2024)
This article examines the teaching of classical Islamic texts (or kitab kuning) in traditional Islamic educational institutions in contemporary Gayo Land. The study is based on research conducted at Dayah Bustanul Arifin 2 in Bener Meriah Regency, Aceh Province, Indonesia. This research is a qualitative research, where data collection is done with: interviews, observations, and documentation, with the data subsequently analyzed using the Miles and Huberman analytical model. The article demonstrates that Dayah Bustanul Arifin 2 plays a role in transmitting traditional Islamic practices in contemporary Gayo Land. It also confirms the research by Martin van Bruinessen, Karel A. Steenbrink, and Zamakhsyari Dhofier on traditional Islamic educational institutions, pesantren, and kitab kuning. The study finds that pesantren in Aceh, known locally as dayah, are traditional Islamic educational institutions that teach Islamic doctrines according to the views of past scholars, both from the Middle East and the Nusantara region, as expressed in their scholarly works written in Arabic language and script. These works cover a range of religious disciplines and represent the intellectual heritage of the Shafi‘i school, the Ash‘ariyya doctrine, and the Sufism of Imam al-Ghazali. The use of classical teaching methods such as sorogan, bandongan, and memorization further underscores that Dayah Bustanul Arifin 2 reinforces and transmits traditional Islamic practices in contemporary Gayo Land. This also affirms that dayah, as a traditional Islamic educational institution in Aceh, retains its resilience and appeal to advance and develop into a professional educational institution.